The Role of Conformational Dynamics in Antigen Trimming by Intracellular Aminopeptidases - Papakyriakou, Athanasios; Stratikos, Efstratios (Frontiers in Immunology, 2017)
Antigenic peptides presented by the major histocompatibility complex class I (MHC-I) molecules for recognition by cytotoxic T-lymphocytes are processed by members of the oxytocinase sub-family of M1 aminopeptidases ERAP1, ERAP2 and IRAP. These three homologous zinc metallopeptidases trim N-terminally extended precursor antigenic peptides down to the correct length for loading onto the MHC-I but can also destroy some antigenic peptides by over-trimming, therefore influencing the antigenic peptide repertoire and immunodominance hierarchy. Polymorphic variation has been found to affect their trimming function and predispose to human disease in complex and poorly understood patterns. Structural and biochemical analysis have pointed towards a complicated trimming mechanism that involves a major conformational transition during each catalytic cycle. Here, we provide an overview of current knowledge on the structure and mechanism of action of those enzymes with a focus on the proposed key role of conformational dynamics in their function.